LOOKING BACK WHILE TRAVELING INTO THE FUTURE: THE LEGACY OF GABRIEL A. BERNARDO, A MAN FOR ALL TIME - Vallejo, Rosa M. (Journal of Philippine Librarianship; Vol 27, No 1&2 (2007), 2008)
In the paper delivered on the 28th Gabriel A. Bernardo Memorial Lecture series, Prof. Rosa M. Vallejo shares her personal encounter with him, when she was his student, and later on as his colleague. She re-introduced Prof. Gabriel A. Bernado and highlighted his legacies to the profession and these are the library buildings which he helped build, the library collection which he established and improved, his contribution to the educaiton and training of librarians including the establishment of the library school and library curriculum, establishment of library organizations, and the Philippine National Bibliography. She also showed the paralellisms in their lives noting that they both were accidental librarians who started their careers in the cataloging section but made significant contributions in the profession. She ends her presentation with her statement of hope that the future has so much in store for librarians if they continue to realize the dreams of Prof. Bernardo.
Keywords: Bernardo, Gabriel A.--Biography, Libraries--Buildings--Philippines, Library--Associations--Philippines, Libraries--History--Philippines, Library education--History--Philippines